COMPOSITE LEVER METHOD FOR POWER FLOW ANALYSIS OF LOOP-TYPE COMPOUND EPICYCLIC GEAR SYSTEM - XU Lin; LIU Kai; CUI YaHui; WANG HongJiang; ZHANG BaoFeng; LIU XiaoLin (Jixie qiangdu)
Due to the complicated structure of the loop-type compound epicyclic gear system, the torque and power relationship between the basic components in the system is complex and variable, forming a variety of power flow types. In order to quickly judge the power flow type of the system during the design process, a composite lever analysis method is proposed. Based on the lever model of a single epicyclic gear train, combined with the structural characteristics of the coupled system, used the superposition principle, a composite lever model reflecting the characteristics of the loop system is established. Then the application method of this model during analyze the characteristics of single loop system is introduced. This composite lever model is found to intuitively reflect the speed, torque and power relationship among the basic components, and then derive the power flow type of the single loop system. The values of the above characteristics can also be calculated by the force arms of the model that reflect the characteristic parameters of the epicyclic gear systems. On this basis, the application of this method in the power flow analysis of dual-loop system is introduced, which provides a new idea for the analysis of multi-loop system.